2020
DOI: 10.1155/2020/4878635
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Risk Factors for Exacerbations in Children with Adenoviral Pneumonia

Abstract: Purpose. The aim of this work was to analyze clinical features and laboratory findings of children with adenovirus pneumonia and guide clinical diagnosis, treatment, and assessment of disease severity. Material and Methods. Retrospective analysis of clinical data of 285 children with adenoviral pneumonia who were hospitalized in Wuhan Children’s Hospital from December 2018 to October 2019. According to the assessment criteria for severe pneumonia, it was divided into the severe group (92 cases) and the nonseve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
8
17
0
Order By: Relevance
“…Wheezing and shortness of breath was more frequent in the severe group. Patients with severe HAdV infections have prolonged fever and required longer hospitalization which was consistent with Wuhan report [ 30 ]. It is different in severity in HAdV infection under the age, environmental status, and immunological status of the patient.…”
Section: Discussionsupporting
confidence: 87%
“…Wheezing and shortness of breath was more frequent in the severe group. Patients with severe HAdV infections have prolonged fever and required longer hospitalization which was consistent with Wuhan report [ 30 ]. It is different in severity in HAdV infection under the age, environmental status, and immunological status of the patient.…”
Section: Discussionsupporting
confidence: 87%
“…The previous studies showed that HAdV-7 causes a more severe disease than the other serotype, with a higher intensive care unit admission rate and a longer length of hospital stay (20). The underlying mechanism may be related to a higher viral load and inflammatory response (5,21,22). In the present study, the median age of all cases was 1.50 years, with 100 cases (80.6%) younger than 3 years old.…”
Section: Discussionsupporting
confidence: 44%
“…In fact, imaging examinations are widely used. A common belief is that patients with suspected pneumonia should undergo chest X-ray examination once they are admitted to the hospital [ 12 , 13 ]. Sometimes sputum microscopy and sputum culture are also performed to understand the types of pathogenic bacteria to assist in the diagnosis and treatment of some complex and refractory cases.…”
Section: Principle and Overviewmentioning
confidence: 99%